Audit of diagnosis and management of placenta praevia. (18th April 2012) - Addley, S; Campbell, P; Zawislak, A
Abstract : Objective: Assess performance in diagnosis and management of placenta praevia. Setting: Tertiary referral hospital (6000 deliveries per annum) Method: Retrospective case note audit of all cases of placenta praevia at delivery over a 12 month period. Criteria and standards taken from RCOG Greentop guideline 27. Results: Twenty-eight women were included. Mean age 33 and mean parity.1 Previous history of caesarean delivery in 7 cases. At routine 20 week scanning placental localisation was documented in 93%. Follow up imaging at 32 weeks was performed in 96% (trans-abdominal 89%, trans-vaginal 7%). MRI scan was performed in 2/7 women with previous Caesarean delivery. Sixteen women (50%) were delivered by elective Caesarean section of which 8 (50%) were before 38 weeks. Ten women (36%) were delivered by emergency Caesarean section and 2 patients had normal deliveries. A Consultant Obstetrician was present for delivery in 94% of elective and 50% of emergency deliveries. Of women undergoing Caesarean section, consent for haemorrhage, transfusion and hysterectomy was 96%, 85% and 73% respectively. Conclusion: The imaging modalities of transvaginal ultrasound and MRI should be utilised more frequently in the diagnosis of placenta praevia. Consultant presence on labour ward out-of-hours would lead to enhanced supervision at emergency deliveries.